The Prevalence of Overweight and Obesity Among Aging Female Inmates. (July 2015) - Leigey, Margaret E.; Johnston, Mary E.
The purpose of this study was to examine the prevalence of overweight and obesity in a sample of older female inmates ( N = 458). Results indicate that 34% of older female inmates were overweight and 36% were obese; similar percentages were noted for the general population. Race and age were found to be significantly associated with the body mass index categories of healthy weight and obese. White inmates were significantly more likely to be of a healthy weight and significantly less likely to be obese than Black inmates. Age was positively associated with healthy weight and negatively associated with obesity. These two variables remained significant even after they were introduced into logistic regression models predicting healthy weight and obesity. Findings indicate the need for programming to improve the health of this population.